Investigation of the added mass method for seismic design of lock gates. (15th January 2017) - Buldgen, Loïc; Caprace, Jean-David; Rigo, Philippe; Le Sourne, Hervé
Highlights: The added mass method is investigated in details. Modeling fluid-structure interaction by the added mass method is discussed. Numerical results obtained by the added mass method are analyzed. The discrepancies with more elaborated models are deeply investigated. The effect of damping is pointed out. Solutions are suggested to improve the added mass method. Abstract: During an earthquake, lock gates are subjected to additional pressure since the water contained in the chamber is put into motion by the earthquake. It is difficult to assess the level of this pressure because the system is affected by a fluid–structure interaction. The gate deformations have an effect on the water pressure, which in turn affects the gate vibrations. A common approach, referred to as the added mass method, consists of simulating the fluid action by distributing lumped masses over the gate. However, this method has been questioned, since the calculation of the lumped masses is usually based on the Westergaard formula, which was derived assuming a perfectly rigid structure. Consequently, fluid–structure interactions may not be captured correctly. This paper proposes to investigate the validity of this approach for such problems and to explain why it might not be conservative. The numerical solutions of an added mass model and a fluid–structure interaction model are confronted. The results indicate that the added mass method may eventually lead to conservative results depending on the type of damping used in the model. Based on these observations, some recommendations are suggested to improve the design of lock gates subjected to earthquakes.